Dermatological Manifestations in Immunocompromised Pediatric Patients on Chemotherapy: A Cross-sectional, Observational Study - Tulika Rai; Rajendra Kumar Mahawar; Priyanka Aggarwal (Clinical Dermatology Review)
Background: Pediatric patients on chemotherapy suffer from various dermatoses due to immunosuppression or due to cutaneous adverse effects of chemotherapy. There is a paucity of literature from our country about the pattern of dermatoses in these patients. Objectives: This study has been conducted to know the pattern of dermatological manifestations in immunocompromised pediatric patients. Materials and Methods: All patients who attended the outpatient department of the division of pediatric hemato-oncology of our hospital and who were diagnosed with hematological and solid organ malignancy were screened. Those children whose guardians were willing to give consent and who fulfilled the inclusion and exclusion criteria were included in the study. The design of the study was cross-sectional. At the visit, demographic data, drug history, and history of any chronic disease were collected. The diagnosis of mucocutaneous manifestations was made by the dermatologist mainly on clinical findings. Special investigations such as potassium hydroxide mount for fungus and Tzanck smear were done in few patients when indicated. Results: A total of 76 patients were enrolled in the study. The ages of the patients ranged from 1 to 18 years with the mean age (years ± standard deviation) being 8.27 ± 4.24 years. A total of 8 patients (10.5%) had fungal infections. Ten patients (13.1%) had viral infections and six (7.9%) patients had bacterial skin infections. Generalized xerosis was the most common cutaneous manifestation which was seen in 13 patients (17.1%), followed by generalized hyperpigmentation, injection site reactions, and nevi (≤10 in number) in 10 patients (13.2%) each. In mucosal findings, mucositis was the most common manifestation seen in 13 patients (17.1%). In hair changes, anagen effluvium was the most common finding seen in 30 patients (39.5%). Discussion: Mucocutaneous findings are common in pediatric patients on chemotherapy. Prompt diagnosis and treatment reduce morbidity and improve the quality of life in these patients. Conclusion: Mucocutaneous findings are common in pediatric patients on chemotherapy due to cutaneous adverse effects of chemotherapy and immunosuppression.